Kinds of Scientific Rationalism: The Case for Methodological Liberalism - Scott Scheall (Duke University, Center for the History of Political Economy (CHOPE), 2015)
The present paper considers the implications of the postulate that the activities of scientists constitute complex phenomena in the sense associated with the methodological writings of the Nobel Prize-winning Austrian economist, methodologist, and political philosopher, F.A. Hayek. Although Hayek wrote extensively on the methodology of sciences that investigate systems of complex phenomena, he never addressed the possibility that science itself is such a system. The application of Hayek's method ology of sciences of complex phenomena to science itself implies some minimal criteria for explanations of scientific rationality. If science is complex in Hayek's sense, then scientific belief may be rational in more than one way. It is argued that a failure to recognize the possibility of multiple kinds of scientific rationality contributes to an error theory of certain unsuccessful accounts of scientific belief in the history of philosophy of science. It is further argued that, where ecological rationality is operative, rational belief requires an element of methodological liberty. It is shown that acceptance of the possibility of ecologically-rational scientific outcomes–a view here dubbed methodological liberalism–is closely related to Hayek's denial of the possibility of a successful scientism, a denial crucial to his arguments against socialism and Keynesian macroeconomics.
Keywords: B29; B31; B41; P11; 330; F.A. Hayek; philosophy of science; complex phenomena; ecological rationality; methodological liberalism